Pengenalan Teknologi Telekomunikasi pada Generasi Muda dalam Menyongsong Era Baru Teknologi Generasi Kelima (5G) - Bengawan Alfaresi; Feby Ardianto; Muhammad Hurairah; Taufik Barlian; Rika Noverianty (Universitas Mataram, 2020)
The development of telecommunications technology has developed very rapidly. This is in line with the increase in internet data traffic which is growing tremendously. The use of the Internet has been used in all layers of the age segment both the older generation to the younger generation. Global competition in the future is very tight and required knowledge of technology, especially telecommunications technology. This is the basis of community service activities for young people to be given knowledge and education about telecommunications technology and its development and to prepare young people to welcome the 5G era to have competitiveness to face the competition map going forward. In this dedication activity, the method used is direct material exposure to students with the implementation of pre and post-tests as material for evaluating activities. Community service activities carried out in Palembang Muhammadiyah 6 Junior High School with a duration of community service activities for 1 day. The number of students who took part in the service was 60 people. In this service, it was found that almost all students have used the Internet with various uses both in the use of email, social media and social messenger, where Facebook is the most favorite social media for junior high school students. From the results of the pre and post-test evaluation, it was found that the level of student retention regarding telecommunications has increased.